Cu-Ni bimetal integrated TiO2 thin film for enhanced solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Saikia, Pranjal; Gopinath, Chinnakonda S. (Solar RRL, 2020)
A series of non-noble Cu-Ni bimetallic catalysts is prepared with different molar proportions of metals. Of these bimetallic catalysts, 1 wt% is subsequently integrated with titania P25. The catalysts are evaluated for solar hydrogen generation under 1 sun condition in both the powder and thin film forms. All the photocatalysts in the thin film exhibit an 8-24 times higher hydrogen yield (HY) compared with the corresponding particulate counterpart. The highest HY (41.7 mmol h(-1) g(-1)) is demonstrated for the photocatalyst Cu-Ni/TiO2 (CNT; 1:1 = Cu:Ni) in the thin film form, which is 24 times higher than that with its powder counterpart (1.75 mmol h(-1) g(-1)) and exceeds the performance of other Cu-Ni/TiO2 compositions. This enhanced activity in the thin film can be ascribed to improved absorption of visible light and an effective separation of photogenerated charge carriers at the interface of Cu-Ni/TiO2 leading to better charge carrier utilization.
Keywords: bimetals; energy conversion; Hydrogen; Photocatalysis; solar energy

Rationally designed, efficient, and earth-abundant Ni-Fe cocatalysts for solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala Prabhakar; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2021)
Developing highly efficient and affordable catalysts for solar hydrogen (H-2) generation is crucial, and employing a cocatalyst from earth-abundant elements has a critical role to play. In this context, different compositions of earth-abundant Ni-Fe alloy (1:1, 1:3, and 3:1) have been prepared by hydrothermal method; subsequently, 1 wt % of these Ni-Fe cocatalysts were integrated with TiO2-P25 and thoroughly characterized. The resultant catalysts have been evaluated for solar H-2 production, in powder and thin film forms, under one sun condition and in direct sunlight. Interestingly, all the catalysts in the thin film form exhibit superior hydrogen yield (HY), up to 27 times higher activity than its powder counterpart. Among the photocatalysts, Ni-Fe/TiO2 (3:1 = Ni/Fe; NFT31) composition exhibits the best HY in thin film (8.27 mmol.h(-1).g(-1)) and exceeds all other compositions of catalyst. It is also to be reported that HY measured for the powder form with 1 mg shows 3-17 times higher activity than that measured with 25 mg. This is mainly attributed to effective solar light absorption with a smaller amount of photocatalyst either spread over large area in a thin film form or well-dispersed in suspension forms. Furthermore, the enhanced activity obtained with Ni-Fe/TiO2 photocatalysts is also ascribed to strong electronic integration of Ni-Fe cocatalyst with TiO2 and higher performance obtained with a thin film is attributed to increased charge carrier generation and subsequent charge separation and effective utilization. A decrease in work function of TiO2 by 0.6 eV was observed after its integration with cocatalyst in NFT31.
Keywords: Cocatalyst; Hydrogen; Ni-Fe alloy; solar energy; TiO2; water splitting